Correlation of rheumatoid factor serotypes and computed tomography findings in rheumatoid arthritis related interstitial lung disease - Sakthiswary Rajalingham; Radhika S; Syahrul Sazliyana Shaharir; Abdul Wahab A (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
The most common extra-articular manifestation of rheumatoid arthritis (RA) is interstitial lung disease (ILD). RA related ILD (RA-ILD) is associated with significant morbidity and mortality. The main objective of this study was to determine the correlation between the rheumatoid factor (RF) serotypes and the severity of RAILD based on computed tomography (CT) findings. We recruited a total of 100 RA patients who were tested for IgA RF, IgG RF and IgM RF and had high resolution CT chest performed. Seventy-two patients had ILD changes on HRCT of the chest and were included in this study. We found that the the CT scores for ground glass showed significant positive correlation with disease duration and IgA RF levels whereas the fibrosis scores had significant relationship with multiple clinical covariates i.e age, disease duration, IgA RF levels, IgG RF levels and anti-CCP levels. On multivariate analysis, only IgA levels remained significantly (p<0.05, standardized beta coefficient = 0.604) associated with the ground glass scores. Regarding the fibrosis scores, IgA RF levels and age were independent predictors based on multivariate analysis after adjusting for confounders, with p scores of <0.05 and 0.02, respectively. In conclusion, the IgA RF was the only serotype which was independently associated with the severity of RA-ILD.